Hopping ahead of climate change : snowshoe hares, science, and survival - Collard, Sneed B. (Bucking Horse Books, 2016)
Scientists seek to answer the critical question "Can snowshoe hares and other animals that change their coat color each winter adapt to shorter winters caused by climate change?"